Letter Writing - Selsdon, Esther (Glasgow HarperCollins, 2001)
The guide offers: practical advice on the techniques of good letter writing; help with finding something to say and in planning your letter, for both tricky and ordinary occasions; guidelines for letters for all occasions, both formal and informal; and help with grammar and punctuation.
Includes Appendix.
Keywords: Letter Writing -- English Language--Rhetoric -- Electronic Mail Messages